Studi Pengadaan Barang dan Jasa Pemerintahan Berbasis Elektronik (E-procurement) Dalam Mewujudkan Tata Kelola Pemerintahan Yang Baik di Kabupaten Kubu Raya - Putra, Prihantana; Amiruddin, Denie; Febriany, Tri Atika (Faculty of Law, Universitas Muhammadiyah Pontianak, 2024)
This research aims to determine and describe Electronic-Based Government Procurement of Goods and Services (E-procurement) in Realizing Good Governance in Kubu Raya Regency. This research uses sociological or empirical legal research, where the data required is primary data, namely data obtained directly from the first source, namely community behavior and secondary data consisting of primary legal material, secondary legal material and tertiary legal material. The research results show that the procurement of goods and services through E-Procurement in Kubu Raya Regency has been carried out quite well and is in accordance with the seven 7 (seven) principles of Good Governance and 12 (twelve) Tender stages as contained in the Procurement General Overview Information Book Government Goods/Services, the Role of PBJ in National Development.pdf of 2020 and Presidential Regulation Number 12 of 2021 concerning Amendments to Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods/Services. Keywords: Procurement of Goods and Services, E-Procurement, Good Governance.